Influence of work-life balance towards level of job satisfaction among research academics in Malaysia - Zainal Badri, Siti Khadijah (2015)
Malaysian Research University academics often exposed to the issues of work-life balance. Work-life balance is suggested as one of potential factor which contribute to the level of job satisfaction among academics. Imbalance between work and life may cause low level of job satisfaction while balance will trigger high level of job satisfaction. This paper aims to foresee the effect of work-life balance towards job satisfaction among academicians in Malaysia. This study is a preliminary study which utilized a survey method to gather the data. A total of 97 respondents were participated in this preliminary study which gathered thru online survey.PASW 18 was executed to analyze the data. Correlation was used to identify relationship between work-to-family enrichment and work-to-family conflict towards job satisfaction. While regression was executed to identify the effect of work-to-family enrichment and work-to-family conflict towards job satisfaction. Result had indicated that work-to-family enrichment and work-to-family conflict significantly influence job satisfaction. In this paper, the researchers discuss the preliminary result of this study and how this study contributes to the knowledge enhancement in area of work-life balance in academia setting.